Turnover Intention: The Impact of Work Environment, Job Compensation Through Job Satisfaction - Shara Rahayu Saputri; Ria Mardiana; Maat Pono (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
This research aims to determine the influence of the work environment, work compensation on turnover intention through job satisfaction at PT Albadriyah Wisata. This research method uses quantitative with a sample obtained from 50 respondents. The sampling technique in this research is probability sampling from the population, namely a sampling technique based on chance at PT Albadriyah Wisata with a data analysis method using SPSS. The research results show that the work environment has a positive effect on job satisfaction. Work compensation has a positive effect on job satisfaction. The work environment has a positive effect on turnover intention . Work compensation has a positive effect on turnover intention. Job satisfaction has a positive effect on turnover intention . The work environment has a positive effect on turnover intention through job satisfaction. Compensation has a positive effect on turnover intention through job satisfaction.